2023
DOI: 10.1093/ntr/ntad003
|View full text |Cite
|
Sign up to set email alerts
|

Vaping Dose, Device Type, and E-Liquid Flavor are Determinants of DNA Damage in Electronic Cigarette Users

Abstract: Introduction Despite the widespread use of electronic cigarettes, the long-term health consequences of vaping are largely unknown. Aims and Methods We investigated the DNA-damaging effects of vaping as compared to smoking in healthy adults, including “exclusive” vapers (never smokers), cigarette smokers only, and nonusers, matched for age, gender, and race (N = 72). Following biochemical verification of vaping or smoking stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Additionally, flavoring compounds associated with common flavor names (eg, fruit) often vary across brands, which precludes accurate comparisons of their toxicological impact. Our review found 11 studies 14,17,18,22,28,32,34,39,52,60,64 that directly compared flavors against one another; however, only menthol and tobacco were included in more than 2 studies. Notably, tobacco flavoring appeared to be generally less harmful than the other flavors studied.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, flavoring compounds associated with common flavor names (eg, fruit) often vary across brands, which precludes accurate comparisons of their toxicological impact. Our review found 11 studies 14,17,18,22,28,32,34,39,52,60,64 that directly compared flavors against one another; however, only menthol and tobacco were included in more than 2 studies. Notably, tobacco flavoring appeared to be generally less harmful than the other flavors studied.…”
Section: Discussionmentioning
confidence: 99%
“…Tommasi et al 32 Oral epithelial cells from e-cigarette users displayed a dosedependent increase in DNA damage vs nonsmoking controls. There was no difference in DNA damage levels between e-cigarette users and smokers.…”
Section: Histological Immunosupression or Infectivitymentioning
confidence: 99%
See 3 more Smart Citations